1979
DOI: 10.1021/ja00510a015
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of [n-Bu4N+][S3N3-] and the vibrational assignments and electronic structure of the planar six-membered ring of the trisulfur trinitride anion

Abstract: Die Titelverbindung kristallisiert in P21/n mit Z=4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

1981
1981
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 4 publications
3
34
0
2
Order By: Relevance
“…2 where it is to be noted that, in addition to the .rr "bonding orbitals", the degenerate antibonding .rr* orbitals 2e" are also fully occupied. Bojes et al (6) further characterized this anion in terms of bond orders and charge densities and all six SN bonds were found to be the same, all three nitrogens were equivalent, and all three sulphurs were equivalent. 'To whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…2 where it is to be noted that, in addition to the .rr "bonding orbitals", the degenerate antibonding .rr* orbitals 2e" are also fully occupied. Bojes et al (6) further characterized this anion in terms of bond orders and charge densities and all six SN bonds were found to be the same, all three nitrogens were equivalent, and all three sulphurs were equivalent. 'To whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently a reasonable representation of the ~o l e c u l a r framework is a "hexagon" with bond lengths of 1.60 A and internal angles of 120°, i.e., the symmetry point group of the nuclei is D,,,. The S3N,-anion has 34 valence electrons and, using a Hartree-Fock-Slater (HFS) single determinant wavefunction, Bojes et al reported (6) that 10 of these were .rr electrons. Thus, the S3N1-anion is a .rr "electron-rich" system (7).…”
Section: Introductionmentioning
confidence: 99%
“…AD iniiio Hartree-Fock-Slater SCF calculations show that it is a six orbital 107-electron system in which the degenerate T:* levels are fully occupied (1,4) and this view of the electronic structure has been confirmed by experiment (2). Some It has been claimed that the dark red amorphous solid which prccipitates when S2N2 reacts with I, in boiling inert solvents is S,N,I (8c).…”
Section: \ @ ?mentioning
confidence: 80%
“…The trisulfur trinitride anion, SIN,-, has been thoroughly I characterized both structurally ( 1 ) and spectroscopically (ir and…”
Section: Introduction Omentioning
confidence: 99%
“…Similar ideas took root in cyclothiazene chemistry in the 1970s, with seminal papers by Gleiter (7) and Banister (8). The structural stability associated with aromatic (4nf2) T-electron counts was recognized, and important examples of new aromatic systems, e.g., the binary rings S , N , (9) and s,N,' + (10) and heterocyclic dithiatetrazocines R2C2N,S2 (1 l ) , were identified. The electron richness of these heterocycles, coupled with the differing electronegativities of their constituent atoms (S and N), leads to highly polarizable T-systems (12).…”
Section: Aromatic and Anti-aromatic Ringsmentioning
confidence: 86%